PERTUMBUHAN SEMAI CEMPAKA (Elmerrillia ovalis (Miq). Dandy) PADA MEDIA TUMBUH YANG DITAMBAHKAN BERBAGAI JENIS SERESAH - Tomas, Tuti Yanti; Yusran, Yusran; Wulandari, Retno; Wahyuni, Dewi (Universitas Tadulako, 2021)
This research was conducted from July to October 2020, at the Management Center For Palu-Poso Protected Forest River Area Permanent Nursery, which is located in the Tadulako University campus area, Palu, Central Sulawesi. This study aims to determine the effect of the growing medium added with various types of litter on the growth of Cempaka (Elmerrillia ovalis (Miq) Dandy) seedlings. This study used a completely randomized design (CRD), which consisted of 4 types of plant leaf litter, namely: S0 = Soil without the addition of litter (control) S1 = Soil + Candlenut leaf litter (3: 1), S2 = Soil + Teak leaf litter, (3: 1), and S3 = soil + coffee leaf litter (3: 1). Each treatment was repeated ten times so that there were a total of 40 treatment units. The results showed that the treatment of Soil + Candlenut Litter (S1) gave good growth in all observation parameters, namely the average height increase of 2.3 cm, the average increase in diameter was 0.29 mm, the increase in the number of leaves on average. an average of 3.5 strands, the average wet weight of the seedlings was 4.57 g, the average root base weight was 1.02 g, the dry weight of the seedlings was 1.03 g, the dry weight of seedling roots was 0.40 g. The highest seed quality index was obtained in the addition of soil and candlenut litter (S1), which was 0.12622 and the lowest was obtained from the control treatment (S0), which was 0.03353.Key words: Cempaka (Elmerrillia ovalis (Miq). Dandy), Legume litter.